(untitled) (Journal of Computational Mathematics, 2005)
This paper is concerned with the stability of theoretical solution and numerical solution of a class of nonlinear differential equations with piecewise delays. At first, a sufficient condition for the stability of theoretical solution of these problems is given, then numerical stability and asymptotical stability are discussed for a class of multistep methods when applied to these problems.